2022
DOI: 10.3389/fonc.2022.799265
|View full text |Cite
|
Sign up to set email alerts
|

FOXP4-AS1 May be a Potential Prognostic Biomarker in Human Cancers: A Meta−Analysis and Bioinformatics Analysis

Abstract: BackgroundCancer is one of the leading causes of death worldwide. Early diagnosis can significantly lower cancer-related mortality. Studies have shown that the lncRNA Forkhead box P4 antisense RNA 1 (FOXP4-AS1) is aberrantly expressed in various solid tumors. A meta-analysis was performed to evaluate the correlation of FOXP4-AS1 with the prognosis of cancer patients and determine the clinical value of FOXP4-AS1 as a potential diagnostic marker.MethodsCorrelational studies from the Web of Science, Embase, OVID,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that lncRNAs are implicated in tumorigenesis and development and are closely related to the prognosis of patients with tumors (Ge et al, 2018;Hu et al, 2021). In previous meta-analyses, FOXP4-AS1 (Zhang et al, 2022b), SNHG15 and SNHG17 (Zhang et al, 2022a) were all linked to the clinicopathological characteristics and prognosis of various malignancies. These findings suggested that lncRNA could be a distinct cancer prognostic biomarker and therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that lncRNAs are implicated in tumorigenesis and development and are closely related to the prognosis of patients with tumors (Ge et al, 2018;Hu et al, 2021). In previous meta-analyses, FOXP4-AS1 (Zhang et al, 2022b), SNHG15 and SNHG17 (Zhang et al, 2022a) were all linked to the clinicopathological characteristics and prognosis of various malignancies. These findings suggested that lncRNA could be a distinct cancer prognostic biomarker and therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…As another research hotspot, 23 studies about SC were included in this study (25,27,36,(44)(45)(46)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Two studies related to circRNA (36,53).…”
Section: Stomach Cancermentioning
confidence: 99%
“…The elevated expression of RP11-357H14.17 and FOXP4-AS1 in GC is linked to reduced overall survival and an unfavorable prognosis. RP11-357H14.17 regulation is also linked with clinical characteristics such as tumor size, differentiation, and metastasis [ 146 , 147 ]. The decreased expression of LINC01939 demonstrated a relation with metastasis and poor prognosis and overall survival in GC [ 148 ].…”
Section: Introductionmentioning
confidence: 99%